miR-590-5p suppresses hepatocellular carcinoma chemoresistance by targeting YAP1 expressionResearch in context - Minjiang Chen; Liming Wu; Jianfei Tu; Zhongwei Zhao; Xiaoxi Fan; Jianting Mao; Qiaoyou Weng; Xulu Wu; Li Huang; Min Xu; Jiansong Ji (EBioMedicine, 2018)
Background: Resistance to chemotherapeutic treatment is a common phenomenon in cancers, especially in hepatocellular carcinoma (HCC). The Hippo signaling pathway has been demonstrated to play a role in tumor initiation, development, and progression. However, little is known about its roles in the HCC chemoresistance. Methods: In this study, real-time PCR and western blotting were used to identify the expression profile of key components of Hippo signaling pathway between chemoresistant and chemosensitive HCC cell lines. In vitro and in vivo loss- and gain-of-function studies were performed to reveal the effects and related mechanism of microRNA-590-5p/YAP1 axis in the chemoresistant phenotype of HCC cells. Findings: We identified yes-associated protein 1 (YAP1) as the major dysregulated molecules in adriamycin (ADR)-resistant HCC cells. YAP1 was profoundly implicated in the chemoresistant phenotype of HCC cells. Furthermore, microRNA-590-5p was revealed as a functional modulator of YAP1. Importantly, YAP1-mediated chemoresistant phenotype was closely related to increased expression of stemness markers and ATP-binding cassette transporters. HCC patients with poor response to transarterial chemoembolization (TACE) treatment had higher protein level of YAP1 than that in the responsive patients. Interpretation: The microRNA-590-5p/YAP axis plays an important role in the chemotherapeutic resistance of HCC cells, suggesting new adjuvant chemotherapeutic directions in HCC. Fund: National Natural Science Foundation of China, Zhejiang Province Medical and Health Care Key Project, Experimental Animal Science and Technology Projects of Zhejiang Province, Public Welfare Technology Application Research Project of Lishui, Chinese Medicine Science and Technology Projects of Zhejiang Province. Keywords: microRNA-590-5p, YAP1, Liver cancer, Transarterial chemoembolization, Chemotherapy, Doxorubicin